In vitro Anti-inflammatory, Antioxidant and Membrane Stabilization Activities of Leaf Extracts of Byttneria pilosa Roxb (Bangladesh Pharmaceutical Journal, 2024)
This current research work was conducted an investigation into the biological activities of various fractions of Byttneria pilosa Roxb. (Family: Sterculiaceae) and analyze the chemical compositions. Preliminary examination of the raw fractional extractives identified the presence of alkaloids, glycosides, flavonoids, saponins, reducing sugars, and tannins. The standard was acetyl salicylic acid for heat-induced method to evaluate the anti-inflammatory and membrane-stabilizing properties. The crude ethanol extract displayed a moderate activity, inhibiting albumin denaturation by 44.7% compared to the positive control. All three extractives also demonstrated significant (p